A comparative analysis of clinical, functional and morphological results of femtosecond, trans-epithelial and standard corneal collagen cross-linking - V. V. Neroev; A. T. Khandzhyan; O. G. Oganesyan; A. V. Penkina; K. B. Letnikova (Российский офтальмологический журнал, 2018)
Purpose: to compare clinical, functional and morphological results of treatment of progressing keratoconus by femtosecond, trans-epithelial and standard corneal collagen crosslinking. Material and methods. 114 patients aged 18-35 (148 eyes) with progressing keratoconus of stages I-III and iatrogenic keratectasia were divided into three groups. Group 1 (39 patients, 47 eyes) received femtosecond corneal collagen crosslinking; group 2 (33 patients, 45 eyes) underwent transepithelial crosslinking and group3 underwent crosslinking performed with standard technique. Results. The analysis of data of confocal microscopy performed 1 year after femtosecond and standard corneal collagen crosslinking revealed the effect of cross linkage in the anterior and middle corneal stroma, an increased density of the extracellular matrix, regeneration of subepithelial and stromal nervous fibers, and keratocyte repopulation. 1 year after trans epithelial crosslinking, keratocyte population was restored. Slight folding in the anterior stroma was observed due to the cross linkage effect. Conclusion. The preserved epithelial layer of the cornea reduces the risk of infectious complications on the eroded surface of the cornea, diminishes visual discomfort and sensation of pain in patients in the early postoperative period, and shortens the rehabilitation period. After trans-epithelial corneal collagen crosslinking, no pronounced effect of cross linkage in the stroma was observed. The available weak positive result justifies the recommendation to use this technique in children, patients with thin cornea, those likely to develop complications during reepithelization, and as a preventive measure in cases of slow progression rate // Russian ophthalmological journal. 2017; 10 (2): 47-53. (in Russian). doi: 10.21516/2072-0076-2017-10-2-47-53.